Effect of alcoholic extract of olea europaea leaves on some lipid profile in rabbits - Zainab Ibrahim Al-Lebawi (Al-Qadisiyah Journal of Pure Science, 2017)
The present study was conducted to knowledge the effect of alcoholic extract of olea europaea leaves on some biochemical parameters in rabbits. Fourteen animals of rabbits were randomly divided into two groups ,control group was exposure to heat stress and given distilled water ,treated group was exposure to heat stress and given 1000mg/kg of alcoholic extract of olea europaea leaves for 30 days .Blood samples were collected after 30 days to do some biochemical parameters.The results showed a significant decrease (P<0.05) in cholesterol concentration ,low density lipoproteins (LDL) concentration and triglycerides concentration in treated group compared with control group.